Welfare Economics and Rationing - Haraldson, W. C. (Quarterly Journal of Economics, 1943)
Journal Article Welfare Economics and Rationing Get access W. C. Haraldson W. C. Haraldson New York City Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 58, Issue 1, December 1943, Pages 146–148, https://doi.org/10.2307/1885762 Published: 01 December 1943